Crescimento micelial in vitro de cinco linhagens de Agaricus bisporus submetidas a diferentes condições de temperatura - De Andrade, Meire Cristina Nogueira (2010)
The in vitro mycelium growth of Agaricus bisporus strains ABI-05/03, ABI-06/04, ABI-04/02, ABI-06/05 and ABI-01/01 was evaluated in solid culture media made up of compost. Evaluations were performed by means of measurements of four diameters of the colonies, every 48 hours, during 12 days of incubation in darkness under 20 and 25°C. The experimental design consisted of randomized blocks, using the Tukey test to compare averages. Based on the obtained results, it was verified that: mycelium growth of A. bisporus is influenced by the temperature of incubation; the temperature of 25°C was more favorable to the mycelium growth of all A. bisporus strains; under the temperature of 20°C, the best growth was obtained with strains ABI-06/05 and ABI-01/01 and, under the temperature of 25°C, strain ABI-01/01 showed significantly higher growth than all other strains.